Determination of sexual maturity of Indonesian box turtle (Cuora amboinensis couro) based on straight carapace length - Daniel Leonardo; Pudji Srianto; Iwan Sahrial Hamid; Boedi Setiawan; Djoko Legowo; Hani Plumeriastuti (Ovozoa: Journal of Animal Reproduction, 2022)
Predicting the turtle's reproductive status and sexual maturity is necessary for ex-situ breeding and conservation program. The histology of the seminiferous tubules of the Indonesian box turtle (Cuora amboinensis couro) at various ages has not been studied much. This study aims to develop equations to predict the sexual maturity of Indonesian box turtles based on straight carapace length (SCL). Six turtles with SCL sizes 10-21 cm were sacrificed and their testes were taken for morphometric measurements and histological preparations for Hematoxylin Eosin staining. Pearson's correlation of SCL with testicular maturity parameters was analyzed, followed by Anova Regression. The results showed that there were differences in the morphometry and topographic anatomy of the Indonesian box turtle testes between SCL below 15 cm and above 15 cm. Six turtles with SCL size of 10-21 cm were sacrificed and their testes were taken for morphometric measurements and histological preparations for Hematoxylin Eosin staining. Pearson's correlation of SCL with testicular maturity parameters was analyzed, followed by Regression Anova. The results showed that there were differences in the morphometry and topographic anatomy of the Indonesian box turtle testes between SCL below 15 cm and above 15 cm.